Modelling fine-scale distribution and relative abundance of harbour porpoises in the Southern Bight of the North Sea using platform-of-opportunity data. (24th May 2020) - Bouveroux, Thibaut; Waggitt, James J.; Belhadjer, Anissa; Cazenave, Pierre W.; Evans, Peter G.H.; Kiszka, Jeremy J.
Abstract: Over the last 25 years, the harbour porpoise ( Phocoena phocoena ) has made a significant return to the Southern Bight of the North Sea and the English Channel due to a shift in distribution from northerly regions. Although the ecological drivers of this return are unclear, this species faces multiple threats in the region, including by-catch and habitat degradation. Ferry-based surveys were conducted year-round between November 2011 and June 2014 to assess the influence of environmental parameters upon the spatiotemporal distribution and relative abundance of harbour porpoises in the Southern Bight of the North Sea. A total of 1450 sightings of harbour porpoises were recorded during the 100 round-trip surveys carried out between Dunkirk (France) and Dover (England). Inter-annual and monthly variations in group size were observed, with largest groups recorded in 2014 (mean = 2.02) and in January (mean = 2.32). The relative abundance showed significant seasonal variation, with peaks recorded during winter months. An inter-annual increasing relative abundance was recorded during the study period. There was a seasonally dependent association with environmental variables, particularly depth, seabed roughness and current speed. Finally, predictions suggest large increases of the relative abundance in offshore habitats during winter months and over the study period.